Clinical, morphological, and molecular genetic predictors of metastatic lesions in the regional lymph nodes in breast cancer - Yu. A. Dergunova; V. V. Podionov; V. K. Bozhenko; V. V. Kometova; M. V. Dardyk (Успехи молекулярной онкологии)
Despite the sufficient amount of data accumulated in the literature, there are still no factors, on the basis of which it would be possible to estimate the regional lymph nodes status in breast cancer with a high degree of accuracy. The review presents literature data relating to the influence of clinicopathological, molecular-biological and genetic characteristics of primary tumor on lymph node metastases. Data of 66 foreign and Russian articles are included.